Maximum Bonus–An Alternative Measure for Trading Gains - Wan, Henry Y. (Review of Economic Studies, 1965)
Journal Article Maximum Bonus—an Alternative Measure for Trading Gains Get access Henry Y. Wan, Jr. Henry Y. Wan, Jr. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 1, January 1965, Pages 49–58, https://doi.org/10.2307/2296331 Published: 01 January 1965